Characteristics of platelet count and size and diagnostic accuracy of mean platelet volume in patients with venous thromboembolism. A systematic review and meta-analysis - Sándor Kovács; Zoltán Csiki; Katalin S Zsóri; Zsuzsanna Bereczky; Amir H. Shemirani (Platelets, 2019)
The purpose of this study was to evaluate the association between platelet (PLT) count and mean platelet volume (MPV) and venous thromboembolism (VTE). Thus, this study reviewed and performed a quantitative synthesis on data from the literature. This meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. 18 studies were included in this paper. A random-effect meta-analysis was conducted for the assessment of heterogeneity using thrombosis place, type of analyzer, type of anticoagulant and incubation time of samples as covariates. A mixed-effect meta-regression was performed based on the subgroup for the whole samples using thrombosis place and method of measurement as moderators for MPV and PLT, respectively. The cumulative estimates and 95% confidence interval (95%CI) of specificity, sensitivity, area under the receiver operator characteristic curve (AUC) and diagnostic odds ratio (DOR) for MPV were calculated using a random effect model. The quality assessments were evaluated according to the quality assessment and diagnostic accuracy tool-2 (QUADAS-2). The primary outcome was the occurrence of VTE. Secondary outcomes included PLT and MPV. Patient with deep vein thrombosis is likely to have a higher value of MPV than control group (P < 0.001). The presence of pulmonary embolism (PE) had no significant effect on the standardized mean difference of MPV between patients and controls. Patients are likely to have less PLT than the control group regarding all studies. However, subgroup analysis demonstrated that this effect was significant for patients with PE (P < 0.05). The summary receiver operating characteristic (SROC) curve indicated that AUC was 0.745 (95% CI: 0.672–0.834). The DOR for MPV was 4.76 (95%CI: 2.3–9.85), with diagnostic accuracy of 0.66.